Relationship Between Species Composition of Butterflyfishes and Coral Cover (Study case: Taka Bonerate National Park) - Ana Faricha; Isa N. Edrus; Sasanti R. Suharti; Rizkie S. Utama; Agus Budiyanto; Abdullah Salatalohi; Suyarso Suyarso (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2020)
The coral reef environment has a strong influence on associated organisms such as fishes, mollusks, and others. Wherein, the butterflyfishes are marine fishes which closely associated with the tropic group as dietary specialization i.e. obligate coral feeder, facultative, and generalist. The obligate may respond only to change in preferred corals and not indicate others. However, generalist show in different response in habitat deteriorates and may allow switching feeding to a less preferred one. Many questions remain about food specific at the species level which may potentially as bio-indicator for coral conditions. Here, we studied the species composition among coral coverage. We explore the environmental degradation in Taka Bonerate National Park impact on food resources and fishes especially for butterflyfishes community. This study focused on family Chaetodontidae with UVC method and UPT method for coral cover. This study was carried out at Taka Bonerate National Park, South Sulawesi between May and June 2019. There were 342 individuals observed and dominated by Chaetodon kleinii, Hemitaurichthys polylepis, Heniochus chrysostomus, C. lunulatus, C. melannotus, C punctatofasciatus, and Forcipiger flavissimus. However, we found a site with diversity index and coral cover has across conditions. Whilst, these benthic communities mostly dominated by Acropora, which may be preferenced by specific species. Butterflyfishes have several types of foraging tasks and may impact in utilizing the coral reef and other social habitats used. The species composition and abundance of butterflyfishes had relations not only by coral coverage but also benthic compositions. However, factors that regulate its specific species distribution and species compositions are still under study.